“Structure-Function Imaging of Lung Disease Using Ultra-Short Echo Time MRI” - Torres, Luis (Acad Radiol, 2019)
The purpose of this review is to acquaint the reader with recent advances in ultra-short echo time (UTE) magnetic resonance imaging (MRI) of the lung and its implications for pulmonary MRI when used in conjunction with functional MRI techniques. UTE MRI has three critical advantages for lung applications: 1) high resolution, whole-lung morphological images without the use of ionizing radiation; 2) mitigation of the short transverse relaxation time constant (T2*) caused by magnetic susceptibility effects prominent at air-tissue interfaces; and 3) in conjunction with a radial acquisition and hard respiratory gating, mitigation of cardiac and respiratory motion artifacts, enabling free breathing exams. UTE MRI clearly shows the lung parenchymal changes due to idiopathic pulmonary fibrosis (IPF) and cystic fibrosis (CF). The use of UTE MRI, in conjunction with established functional lung MRI in chronic lung diseases, will serve to mitigate the need for computed tomography (CT) in children. Current limitations of UTE MRI include long scan times, poor delineation of thin walled structures (e.g. cysts and reticulation) due to limited spatial resolution, low signal to noise (SNR), and imperfect motion compensation. Despite these limitations, UTE MRI can now be considered as an alternative to multi-detector CT for the longitudinal follow up of the morphological changes from lung diseases in neonates, children and young adults, particularly as a complement to the unique functional capabilities of MRI.